Bugs and Drugs: An Integrated Case-Based Microbiology Pharmacology Session on Urinary Tract Infections - Melphine Harriott; Christine Yost (Association of American Medical Colleges, 2014)
Abstract This interactive case study session on urinary tract infections combines basic microbiology with pharmacology (antimicrobials). The overall goal is to review the major pathogens of the urinary tract and to review select antibiotics and their mechanisms of actions, spectrum of activity, and resistance mechanisms. It is intended as a 50-minute small-group activity in which students discuss cases and corresponding questions followed by an instructor-facilitated discussion for each case. Included in this resource is a web-based reading module on urinary tract infections that can be utilized as preparatory reading prior to this session, or may be used alone. This microbiology session aims to reinforce the basic microbiology and pharmacology-related microbiology concepts covered during the introductory microbiology course and to place the pathogens and antimicrobials in context of the urinary tract.